2017
DOI: 10.3389/fimmu.2017.01132
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes and Cancer: The Dynamic Role of the Inflammasome in Tumor Development

Abstract: Chronic Inflammation in tumor microenvironments is not only associated with various stages of tumor development, but also has significant impacts on tumor immunity and immunotherapy. Inflammasome are an important innate immune pathway critical for the production of active IL-1β and interleukin 18, as well as the induction of pyroptosis. Although extensive studies have demonstrated that inflammasomes play a vital role in infectious and autoimmune diseases, their role in tumor progression remains elusive. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 147 publications
0
90
0
Order By: Relevance
“…In addition to the crucial roles in inflammatory and immune responses, emerging evidence has indicated that inflammasomes components are markedly upregulated in various cancers, such as lung, melanoma, oral squamous cell carcinoma, and breast cancer cells [18][19][20][21][22]. In addition, activation of the inflammasome facilitates tumor progression [23,24], suggesting that inflammasomes act as mediators that bridge chronic inflammation and tumorigenesis. Interestingly, in contrast to this notion, it has been also well documented that the suppressive effects on tumor growth by various anticancer agents are mediated through inflammasomes activation, which initiates pyroptotic cell death in cancer cells [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the crucial roles in inflammatory and immune responses, emerging evidence has indicated that inflammasomes components are markedly upregulated in various cancers, such as lung, melanoma, oral squamous cell carcinoma, and breast cancer cells [18][19][20][21][22]. In addition, activation of the inflammasome facilitates tumor progression [23,24], suggesting that inflammasomes act as mediators that bridge chronic inflammation and tumorigenesis. Interestingly, in contrast to this notion, it has been also well documented that the suppressive effects on tumor growth by various anticancer agents are mediated through inflammasomes activation, which initiates pyroptotic cell death in cancer cells [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…(B) Pro-inflammatory function in cancer cells. In cancer cells and myeloid cells (such as TAMs), recognition of pathogen-or damage-associated molecular patterns (PAMPs, DAMPs) induces the assembly/polymerization of the inflammasome molecular complex, which in cancer cells is otherwise often constitutively activated as a result of genetic lesions (Kolb et al, 2014;Kantono and Guo, 2017;Karan, 2018;Karki and Kanneganti, 2019). The inflammasome is composed by a multimerized module formed by a sensor Nod Leucine-Rich Repeat-containing receptor, such as NLRP3, bound to the pyrin domain of the adaptor ASC, which in turn is bound, through its CARD domain, to pro-caspase-1.…”
Section: Asc/tms1 As Tumor Suppressormentioning
confidence: 99%
“…The role of inflammasomes in cancer has been recently discussed elsewhere (Kolb et al, 2014;Kantono and Guo, 2017;Karan, 2018;Karki and Kanneganti, 2019;Van Gorp and Lamkanfi, 2019). We refer readers interested in comprehensive summaries of the field to those reviews.…”
Section: Asc As Inflammasome Adaptor Moleculementioning
confidence: 99%
“…An increasing body of evidence indicates that inflammation is one of the hallmarks of carcinogenesis, allowing the growth and metastasis of tumors (1). The role of inflammation is two-fold: On one hand, the tumor and antigens present on the surface of cells can stimulate effector cell recruitment of the innate immune system, resulting in the destruction of diseased tissue; on the other hand, mere stimulation of the immune response is associated with the development of inflammation, which can stimulate the growth of a tumor through the production of proinflammatory cytokines, thus creating a feedback loop (2). A special role in this process is played by interleukin 1β (IL-1β), which promotes tumor progression, neoangiogenesis, and metastasis (3).…”
Section: Introductionmentioning
confidence: 99%